2021
DOI: 10.3390/buildings11120630
|View full text |Cite
|
Sign up to set email alerts
|

A Scientometric Analysis and Overview of Research on Infrastructure Externalities

Abstract: There is a growing level of concern regarding infrastructure externalities globally. However, most of the previous relevant reviews were undertaken manually and few of them covered all infrastructure systems. This study conducted a scientometric analysis and overview of the research on externalities of all infrastructure systems. The analysis results of 743 articles that were rigorously selected first showed the increasing trend of research interest in infrastructure externalities. Moreover, the results demons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 100 publications
(140 reference statements)
0
8
0
Order By: Relevance
“…The comprehensive literature review of the externalities of highway infrastructures in this study and a scientometric analysis of infrastructure externalities conducted by Zhu et al [11] all showed that there are many research on the needs of transport, the impact of transport, and the externalities of transport, providing a solid scientific knowledge base for the evaluation of the externalities of highway infrastructures. However, there are still research gaps in two main perspectives.…”
Section: Evaluation Of Multiple Dimensional Externalitiesmentioning
confidence: 75%
See 4 more Smart Citations
“…The comprehensive literature review of the externalities of highway infrastructures in this study and a scientometric analysis of infrastructure externalities conducted by Zhu et al [11] all showed that there are many research on the needs of transport, the impact of transport, and the externalities of transport, providing a solid scientific knowledge base for the evaluation of the externalities of highway infrastructures. However, there are still research gaps in two main perspectives.…”
Section: Evaluation Of Multiple Dimensional Externalitiesmentioning
confidence: 75%
“…The development of highway infrastructures comes from the needs of the economy, society, and environment, and conversely, has impacts on these three aspects. The lack of externality evaluation of any dimension will not only bias the view of highway-related externality problems, but also lead to the distortions in the planning and development of highway infrastructures, leading to government failure or market failure for the governance of externalities [11,28,35]. The evaluation indexes in previous research are not comprehensive.…”
Section: Evaluation Of Multiple Dimensional Externalitiesmentioning
confidence: 99%
See 3 more Smart Citations